Criminal defence and procedure: comparative ethnographies in the United Kingdom, Germany, and the United States - Scheffer, Thomas (Palgrave Macmillan, 2010)
"Doing Procedure provides an in-depth comparison of criminal defence work in different legal cultures, showing how defence work is shaped by different regimes and how it influences outcomes"--